Soil nitrogen dynamics and competition during plant invasion: insights from Mikania micrantha invasions in China. Issue 6 (28th December 2020) - Yu, Hanxia; Le Roux, Johannes J.; Jiang, Zhaoyang; Sun, Feng; Peng, Changlian; Li, Weihua
Summary: Invasive plants often change a/biotic soil conditions to increase their competitiveness. We compared the microbially mediated soil nitrogen (N) cycle of invasive Mikania micrantha and two co‐occurring native competitors, Persicaria chinensis and Paederia scandens . We assessed how differences in plant tissue N content, soil nutrients, N cycling rates, microbial biomass and activity, and diversity and abundance of N‐cycling microbes associated with these species impact their competitiveness. Mikania micrantha outcompeted both native species by transferring more N to plant tissue (37.9–55.8% more than natives). We found total soil N to be at lowest, and available N highest, in M. micrantha rhizospheres, suggesting higher N cycling rates compared with both natives. Higher microbial biomass and enzyme activities in M. micrantha rhizospheres confirmed this, being positively correlated with soil N mineralization rates and available N. Mikania micrantha rhizospheres harbored highly diverse N‐cycling microbes, including N‐fixing, ammonia‐oxidizing and denitrifying bacteria and ammonia‐oxidizing archaea (AOA). Structural equation models indicated that M. micrantha obtained available N via AOA‐mediated nitrification mainly. Field data mirrored our experimental findings. Nitrogen availability is elevated under M .  micrantha invasion through enrichment of microbes that participate in N cycling, in turn increasing available N for plant growth, facilitating high interspecific competition.